A new kymogram-based method reveals unexpected effects of marker protein expression and spatial anisotropy of cytoskeletal dynamics in plant cell cortex - Cvrčková, Fatima; Oulehlová, Denisa (Plant methods, 2017)
BACKGROUND: Cytoskeleton can be observed in live plant cells in situ with high spatial and temporal resolution using a combination of specific fluorescent protein tag expression and advanced microscopy methods such as spinning disc confocal microscopy (SDCM) or variable angle epifluorescence microscopy (VAEM). Existing methods for quantifying cytoskeletal dynamics are often either based on laborious manual structure tracking, or depend on costly commercial software. Current automated methods also do not readily allow separate measurements of structure lifetime, lateral mobility, and spatial anisotropy of these parameters. RESULTS: We developed a new freeware-based, operational system-independent semi-manual technique for analyzing VAEM or SDCM data, QuACK (Quantitative Analysis of Cytoskeletal Kymograms), and validated it on data from Arabidopsis thaliana fh1 formin mutants, previously shown by conventional methods to exhibit altered actin and microtubule dynamics compared to the wild type. Besides of confirming the published mutant phenotype, QuACK was used to characterize surprising differential effects of various fluorescent protein tags fused to the Lifeact actin probe on actin dynamics in A. thaliana cotyledon epidermis. In particular, Lifeact-YFP slowed down actin dynamics compared to Lifeact-GFP at marker expression levels causing no macroscopically noticeable phenotypic alterations, although the two fluorophores are nearly identical. We could also demonstrate the expected, but previously undocumented, anisotropy of cytoskeletal dynamics in elongated epidermal cells of A. thaliana petioles and hypocotyls. CONCLUSIONS: Our new method for evaluating plant cytoskeletal dynamics has several advantages over existing techniques. It is intuitive, rapid compared to fully manual approaches, based on the free ImageJ software (including macros we provide here for download), and allows measurement of multiple parameters. Our approach was already used to document unexpected differences in actin mobility in transgenic A. thaliana expressing Lifeact fusion proteins with different fluorophores, highlighting the need for cautious interpretation of experimental results, as well as to reveal hitherto uncharacterized anisotropy of cytoskeletal mobility in elongated plant cells.
Keywords: Microtubules; FH1 (At3g25500); Actin; Anisotropy; Lateral mobility; Variable angle fluorescence microscopy; Kymogram; Structure stability; Lifeact; Spinning disc confocal microscopy